2007
DOI: 10.1111/j.1742-4658.2007.06116.x
|View full text |Cite
|
Sign up to set email alerts
|

G protein‐coupled receptor‐induced Akt activity in cellular proliferation and apoptosis

Abstract: Akt, also known as protein kinase B (PKB), is a serine ⁄ threonine protein kinase that plays a pivotal role in many physiological processes, including metabolism, development, cell cycle progression, migration and survival [1][2][3][4]. The Akt subfamily of protein kinases consists of three isoforms -Akt1, Akt2 and Akt3 (also termed PKBa, PKBb and PKBc) -which are the products of distinct genes. All three proteins share a conserved tertiary structure of an N-terminal pleckstrin homology domain, a kinase domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 80 publications
4
80
1
Order By: Relevance
“…Studies using G q knock-out in mice demonstrated a role of this protein in platelet activation as well as in the development and functioning of the central nervous system and the heart (7,8). Other G q PCRregulated effects have been identified by other methods, including regulation of proliferation (9), the reproductive system (10), brain functioning (6), and more (11). Aside from these G q PCRinduced effects, these central receptors were also implicated in growth arrest or apoptosis in few pathological systems (11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using G q knock-out in mice demonstrated a role of this protein in platelet activation as well as in the development and functioning of the central nervous system and the heart (7,8). Other G q PCRregulated effects have been identified by other methods, including regulation of proliferation (9), the reproductive system (10), brain functioning (6), and more (11). Aside from these G q PCRinduced effects, these central receptors were also implicated in growth arrest or apoptosis in few pathological systems (11)(12)(13).…”
mentioning
confidence: 99%
“…Among all G proteins, the four members of the G q family (G q , G 11 , G 14 , and G 15/16 ) function primarily via activation of phospholipase C-␤ (6). This effector then produces the second messengers inositol trisphospate and diacylglycerol, which further elevate intracellular calcium levels as well as protein kinase C (PKC) activity to induce many intracellular signaling and the plethora of G q PCR-induced effects.…”
mentioning
confidence: 99%
“…The mechanisms of regulating Akt by 5-HT1BR are not fully understood, but it is believed that both ␣-and ␤␥-subunits of G-protein as well as ␤-arrestin are associated with GPCR-induced activation of Akt (DeWire et al, 2007;New et al, 2007;Yang et al, 2009). The finding that GSK3 influences 5-HT1BR-induced activation of Akt further supports the significant effect of GSK3 in 5-HT1BR-regulated signaling.…”
Section: Discussionmentioning
confidence: 66%
“…13) Some G protein-coupled receptors (GPCRs) have been shown to activate the Akt pathway. 14) There are several reports suggesting that the Akt pathway mediates responses to adenosine receptor stimulation: The phosphorylation of Akt and ERK1/2 via the activation of adenosine A 2B receptors regulates the function of glioblastoma stem cells, 15) and the activation of adenosine A 3 receptors induces the activation of Akt in melanoma cells.…”
Section: Discussionmentioning
confidence: 99%